ANALISIS PENGARUH INTERNAL DAN EXTERNAL CORPORATE GOVERNANCE TERHADAP AUDIT REPORT LAG (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021) - Anggun Budiarti; Tarmizi Achmad (Diponegoro Journal of Accounting, 2023)
The study aims to examine the relationship between internal and external Corporate Governance mechanisms on Audit Report Lag in banking companies listed on IDX in 2019-2021. While, the depedent variabel used in this study is audit report lag. The independent variables used are audit committee size, audit committee’s expertise, the number of audit committee’s meetings, independent commissioners’ proportion, and auditor industry specialization and size as moderation variable. This study used the secondary datas using the purposive sampling method to determine the sample of banking companies in 2019-2021, which are listed on Indonesia Stock Exchange. This study determined 45 banking companies with total 135 samples used. This study used multiple linear regression analysis with the classic assumption is done beforehand. A significant negative relationship was observed between the number of audit committee’s meeting and audit report lag. Meanwhile, the other independent variables do not have a significant negative relationship with audit report lag.